Improving Quality of Tahfidz Islamic Boarding Schools through Agrosocial-Based Education Financing Management Practices - Siti Kholifah; Dewi Kumala Sutra; Riduan Nasution; Rifai Rifai; Nurul Hidayati Murtafi’ah (Journal Corner of Education, Linguistics, and Literature, 2022)
The purpose of this study was to describe the implementation of a Agro-Social-based education financing management program. In this research, the writer used a descriptive qualitative. The subjects in this study were the head of the cottage/manager, teachers, and administrative staff at Pondok Tahfidz Nurul Jannah, Jimmy Hantu village, Bogor. Observation, interview and documentation were used in collecting the data. Data analysis techniques are data collection, data reduction, data presentation and conclusions. This research used a validity test using the triangulation technique, which was carried out by comparing information from various sources in the study. This study's results indicate that this education's financing is based on a Agro-Social at Pondok Pesantren Tahfidz Nurul Jannah Jimmy Hantu Bogor. Financing management is carried out based on 3 methods: planning submitted to the Foundation, application at the Tahfidz Nurul Jannah Institution, supervision and reporting to the Jimmy Hantu Foundation.